PELAKSANAAN PEMBELAJARAN MASA PANDEMI COVID-19 PADA LEMBAGA KURSUS DAN PELATIHAN ICC (INTERNATIONAL CAREER COLLEGE) KOTA PEKANBARU - Viana Intan Sabrity Sitompul; Said Suhil Achmad; Daeng Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines the implementation of learning during the Covid-19pandemic at the Pekanbaru City ICC (International Career College) Course andTraining Institute and in this implementation there are initial activities, core activities,and final activities in carrying out learning during the Covid-19 pandemic. . Thepurpose of this study was to describe the implementation of learning during the Covid-19 pandemic at the Pekanbaru City ICC (International Career College) Course andTraining Institute. This type of research is descriptive with a qualitative approach,where the data collection process is carried out by interviewing 4 subjects, namelycontrol informants, core informants 1, core informants 2, core informants 3 withdocumentation included. Based on the results of interviews, researchers found 3indicators, namely: (1) Initial Activities, (2) Core Activities, (3) Final Activities. Thestudy of these 3 indicators is very useful for understanding how the stages of theimplementation process are appropriate in carrying out the Implementation of LearningDuring the Covid-19 Pandemic Period.Key Word: Implementation, Learning, Course Institute, Training